1997
DOI: 10.1177/019262339702500511
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Intrahepatic Arteriovenous Fistulae in a Young Beagle Dog

Abstract: Congenital intrahepatic arteriovenous fistulae, a rare hepatic vascular anomaly, in an 8-mo-old female beagle dog was investigated. The animal showed anorexia, repeated vomiting, hemorrhagic diarrhea, and jaundice for approximately 2 wk. There was mild to severe increase of serum alkaline phosphatase, glutamic-oxalacetic transaminase, glutamic pyruvic transaminase, total cholesterol, total bilirubin, and γ-glutamyl transpeptidase. Macroscopically, the main abdominal organs showed hemorrhagic edema togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Vascular changes, in addition to the presence of multiple intermingling, dilated, and abnormal vessels-including elastolysis, splitting and reduplication of the internal elastic lamina, intimal hyperplasia, mucinous degeneration of the subintima and media, and smooth muscle hyperplasia-have been reported by numerous authors, including Moore and Whiting (1986), Easley and Carpenter (1975), Schaeffer et al (2001), and Yoshizawa et al (1997). All authors also report fibrosis, parenchymal atrophy, and biliary hyperplasia.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Vascular changes, in addition to the presence of multiple intermingling, dilated, and abnormal vessels-including elastolysis, splitting and reduplication of the internal elastic lamina, intimal hyperplasia, mucinous degeneration of the subintima and media, and smooth muscle hyperplasia-have been reported by numerous authors, including Moore and Whiting (1986), Easley and Carpenter (1975), Schaeffer et al (2001), and Yoshizawa et al (1997). All authors also report fibrosis, parenchymal atrophy, and biliary hyperplasia.…”
Section: Discussionmentioning
confidence: 94%
“…Vascular hamartomas and congenital intrahepatic arteriovenous fistulae are rare in dogs (Schermerhorn et al 1997), and there has been only one previously reported case in a laboratory beagle (Yoshizawa et al, 1997). They arise from focal failure of differentiation of the common embryologic anlage into capillary, arterial, or venous structures and represent communications between the hepatic arteries and portal venous radicals, which leads to a retrograde flow of blood within the portal vein (Moore and Whiting 1986).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…66(3): 299-302, 2004 Hepatic arteriovenous fistula is a condition characterized by a communication between the portal or the hepatic vein and hepatic artery. All previous case reports of dogs regarding this condition showed vascular abnormality with communication between the portal and hepatic artery [1,3,6,7,9,13]. Dogs with hepatic arteriovenous fistula usually exhibit ascites and secondary multiple portosystemic shunt (PSS) due to portal hypertension [8,12].…”
mentioning
confidence: 99%